Impact of Pad Material Properties on CMP Performance for Sub-10nm Technologies. (1st January 2019) - Khanna, Aniruddh J.; Kakireddy, Raghava; Jawali, Puneet; Chockalingam, Ashwin; Redfield, Daniel; Bajaj, Rajeev; Fung, Jason; Cornejo, Mario; Yamamura, Mayu; Yuan, Zhibo; Orilall, Chris; Fu, Boyi; et al.
Abstract : It is well known that chemical mechanical polishing (CMP) pads play a dominant role in the overall performance of the polishing process. It is critical to have a fundamental understanding of the impact of the change in the pad mechanical properties on the CMP performance. The stabilization of material removal rates and planarization efficiency (PE) are demonstrated by modification of pad mechanical properties such as storage modulus. For all the pads, removal rate and PE values are compared between wafers polished for a longer time (90 seconds) versus shorter time (15 seconds). It is concluded that for longer polish time, higher removal rate and lower PE results from a drop in the storage modulus. This decrease in the storage modulus is a consequence of an increase in the polish temperature with time. Results indicate that by minimizing the change in storage modulus with temperature, the impact of longer polish time on CMP performance can be minimized.